The shepherd's crown [compact disc, unabridged] : a Tiffany Aching adventure - Pratchett, Terry (Pratchett, Terry. Discworld series., 2015)
Deep in the Chalk, something is stirring. The owls and the foxes can sense it, and Tiffany Aching feels it in her boots. An old enemy is gathering strength. As the fairy horde prepares for invasion, Tiffany must summon all the witches to stand with her to protect her land.